2015
DOI: 10.1016/j.edurev.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Teacher collaboration: A systematic review

Abstract: A B S T R A C T This paper presents a systematic review on teacher collaboration. In total, 82 studies were selected based on predefined selection criteria and reviewed by means of a narrative review method to thematically gather information across the studies. The first aim of this review was to provide an overview of the terminological framework to describe teacher collaboration used in previous research. Collaboration was perceived here as a continuum ranging from mere aggregates of individuals to strong te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
530
0
98

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 635 publications
(644 citation statements)
references
References 75 publications
16
530
0
98
Order By: Relevance
“…Roxå and Mårtensson (2015) argue that collaboration between university teachers takes place in various forms and that collaborative forms of innovation are mainly characterized by a shared responsibility for educational development. However, Vangrieken et al (2015) question the extent to which collaborating university teachers in fact share and follow up on this responsibility. Cox (2004) observed that university teacher's work tradition is largely solitary, with high levels of individual autonomy.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Roxå and Mårtensson (2015) argue that collaboration between university teachers takes place in various forms and that collaborative forms of innovation are mainly characterized by a shared responsibility for educational development. However, Vangrieken et al (2015) question the extent to which collaborating university teachers in fact share and follow up on this responsibility. Cox (2004) observed that university teacher's work tradition is largely solitary, with high levels of individual autonomy.…”
Section: Introductionmentioning
confidence: 99%
“…Such research also predominately focuses on team performance as an outcome and not on team learning (Burke et al 2006;Nicolaides et al 2014). Moreover, research on the influence of team leadership on teacher team learning is lacking, because empirical studies on stimulating collaborative teacher learning are limited (Little 2006;Vescio et al 2008) and mostly do not concern teams but collaboration forms with lower levels of task interdependence and shared responsibility (Brouwer et al 2012;Vangrieken et al 2015). In addition, these studies have mainly been conducted in primary and secondary education, and rarely in higher education (Kezar 2011;Vangrieken et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the 1970s the topic is being transferred to the schooling sector and educational research. In fact, most of the research in this field accredits collaboration to support many positive outcomes such as a better school quality (Goddard, Goddard, & TschannenMoran, 2007;Ronfeld, Matthew, Owens Farmer, McQueen, & Grissom, 2015), healthier teachers (Schaarschmidt, 2005) and -for this study the most important finding -a profound, positive impact on teacher professionalization (Avalos, 2011;Vangrieken, Dochy, Raes, & Kyndt, 2015).…”
Section: Introductionmentioning
confidence: 93%